(untitled) (Bangladesh Heart Journal, 2018)
Background: Dyslipidaemias is one of the major risk factor for Coronary artery diseases (CAD).There is an inverse correlation between high density lipoprotein cholesterol (HDL-C) and the risk of coronary artery disease. Understanding the angiographic characteristics of coronary artery diseases (CAD) in low and normal HDLC patients and its association with severity of CAD is very important for future intervention. Although highdensity lipoprotein cholesterol (HDL-C) is well established predictor of future cardiovascular event, little information is available regarding its correlation with the prevalence and severity of angiographically evaluated coronary artery diseases (CAD). Materials and Methods: This cross-sectional comparative study was conducted in the Department of Cardiology, Sylhet MAG Osmani Medical College Hospital, Sylhet during the period from January 2012 to December 2013. We included 100 patients with coronary artery diseases and divided into two groups. 50 patients with low HDL-C (<40 mg/dl) were taken in study group (Group-A) and 50 patients with normal HDLC (>40 mg/dl) were taken in control group (Group-B) according to inclusion and exclusion criteria. Coronary angiography was performed via the trans-femoral approach using standard techniques. Severity of CAD was determined by vessels score and Friesinger score. Results: The age [51.1 (SD 8.7) years vs 51.4 (SD 8.2) years; p>0.05] and sex [45 (90.0%) male and 5 (10.0%) female vs 41 (82.0%) male and 9 (18.0%) female; p=0.249] were similar in group-A and group-B. The conventional risk did not show any significant difference between low and normal HDL level group such as age, sex, smoking, diabetes mellitus, hypertension, BMI, hypercholesterolaemia, high serum LDL, hypertriglyceridaemia and family history of CAD (p>0.05 each). No significant vessel disease [3 (6.0%) vs 14 (28.0%); p=0.008] and single vessel disease [11 (22.0%) vs 25 (50.0%); p=0.020] were significantly fewer in group A than that of group-B; while double vessel disease [14 (28.0%) vs 5 (10.0%); p=0.039] and triple vessels disease [22 (44.0%) vs 6 (12.0%); p=0.002] were significantly higher in group-A than that of group-B. Friesinger score 0 [3 (6.0%) vs 11 (22.0%); p=0.033] and Friesinger score 1 to 4 [6 (12.0%) vs 24 (48.0%); p=0.01] were significantly fewer in group A than that of group-B; while Friesinger score 5 to 9 [20(40.0%) vs 9 (18.0%); p=0.041] and Friesinger score 10 to 15 [21 (42.0%) vs 6 (12.0%); p<0.004] were significantly higher in group-A than that of group-B. Among all respondents conventional risk factors were not statically significant between the groups. A significant negative correlation was found between serum HDL-C (mg/dl) and number of diseased vessel (r=0.370; p<0.001) and also Friesinger score (r=0.388; p<0.001). Conclusion: It may be concluded that low HDL-C level is associated with angiographically more severe coronary artery diseases reflected by vessels score and Friesinger score as compared to normal or high HDL-C level. Bangladesh Heart Journal 2018; 33(1) : 32-38